A modified polyamide flame retardant plastic and preparation method thereof

The existing polyamide resistance is solved by using glass fibers and adhesives wrapped in flame retardant materials in polyamide flame retardant materials, combining lubricants, antioxidants and toughening agents to form modified polyamide flame retardant plastics. The problem of poor flame retardant effect of combustion materials during combustion has achieved a combination of high mechanical properties and excellent flame retardant properties.

CN118599305BActive Publication Date: 2025-01-14GUANGDONG BOSHIDA NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410577732.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-01-14
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

During the combustion process, existing polyamide flame retardant materials have low flame retardant effects due to the combustion-stimulating effect of glass fibers. At the same time, removing glass fibers or adding flame retardants will lead to a decrease in mechanical properties.

Method used

Modified polyamide flame retardant plastics including flame retardant glass fibers, lubricants, antioxidants, heat stabilizers and tougheners are used to reduce cohesion and increase resistance by wrapping flame retardant materials and adhesives on the glass fibers. ignition performance and form a mesh structure through ultrafine glass fibers and glass grinding fibers to reduce the wick effect.

Benefits of technology

While ensuring mechanical properties, it significantly improves flame retardant performance, reduces the combustion-stimulating effect of glass fiber, enhances the toughness and thermal stability of plastics, and achieves better flame blocking and delaying effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a modified polyamide flame-retardant plastic, which relates to the technical field of polymer materials. The material comprises the following raw materials in parts by weight: 50-70 parts of polyamide resin, 30-40 parts of composite glass fibers, 1-2 parts of lubricants, 1-3 parts of antioxidants, 1-3 parts of flame retardants, 0.1-1 parts of heat stabilizers, and 1-2 parts of toughening agents. The composite glass fibers comprise flame-retardant glass fibers, and a single flame-retardant glass fiber comprises a plurality of ultrafine glass fibers with flame-retardant materials wrapped on the outside, and the plurality of ultrafine glass fibers are bonded by an adhesive to form the flame-retardant glass fibers, which have good flame retardancy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a modified polyamide flame-retardant plastic and a preparation method thereof. Background Art

[0002] Polyamides are synthetic polymers widely used to manufacture a wide variety of shaped articles, including molded parts and injection molded parts, which are often proposed for use in the high-end electrical industry, the electronics industry, and the automotive industry.

[0003] Glass fiber is a common reinforcing material for polyamide, and its main components are silicon dioxide, aluminum oxide, calcium oxide, boron oxide, magnesium oxide, sodium oxide, etc. Glass fiber reinforced composite materials are composite materials made of polyamide as the matrix and glass fiber as the reinforcing material. The composite materials combine the properties of polyamide matrix and glass fiber, and improve the tensile, impact and thermal stability of polyamide itself.

[0004] However, during use, the glass fiber promotes combustion, and this promoting effect is called the "wick effect". It can be considered that the polymer surface is melted and decomposed by heat, and the glass fiber is like a conduit. The liquid of the molten decomposed polymer moves along the glass fiber toward the fire source or high temperature field, and the combustion provides heat. The heat causes the polymer to decompose and produce fuel, and the fuel maintains combustion, forming a cycle, thereby promoting the combustion of polyamide and reducing the flame retardant effect of polyamide.

[0005] However, if glass fiber or similar fillers are removed or excessive flame retardants are added, the mechanical properties of polyamide will drop significantly. Summary of the invention

[0006] The purpose of the present disclosure is to provide a modified polyamide flame-retardant plastic, which has good flame retardancy while ensuring mechanical properties. In order to achieve the above purpose, the present disclosure provides a modified polyamide flame-retardant plastic, which includes the following raw materials in parts by weight: 50-70 parts of polyamide resin, 30-40 parts of composite glass fiber, 1-2 parts of lubricant, 1-3 parts of antioxidant, 1-3 parts of flame retardant, 0.1-1 parts of heat stabilizer, 1-2 parts of toughening agent, the composite glass fiber includes flame-retardant glass fiber, a single flame-retardant glass fiber includes a plurality of ultra-fine glass fibers wrapped with flame-retardant material on the outside, and the plurality of ultra-fine glass fibers are bonded by an adhesive to form the flame-retardant glass fiber.

[0007] The modified polyamide flame-retardant plastic provided by the present invention has good compatibility with polyamide by adding lubricant, which plays a role in reducing the cohesive force between polyamide molecules inside the polyamide, thereby improving the internal friction heat generation of the plastic melt and the fluidity of the melt; the antioxidant helps to inhibit the oxidation and degradation of the polymer by the atmosphere. They can minimize the degradation of polymers during processing, storage and use; after the flame retardant is added, it can effectively prevent, delay or terminate the spread of flames when attacked by external fire sources, thereby achieving the flame retardant effect; thermal stabilizers help to reduce the gradual destruction of modified polyamide flame retardant plastics under the influence of heat, radiation, oxygen and other factors; toughening agents help to increase toughness and improve bearing strength. Composite glass fibers can improve tensile, impact and thermal stability. At the same time, when attacked by external fire sources, the adhesive first melts and fails at high temperatures, and a single flame retardant glass fiber breaks into several ultra-fine glass fibers, destroying the channel for the liquid of the molten decomposition of the polymer to move along the entire flame retardant glass fiber to the fire source or high temperature field, reducing the "wick effect" of the glass fiber and the combustion-supporting effect of the glass fiber, thereby enhancing the flame retardant ability of the modified polyamide flame retardant plastic. At the same time, after a single flame retardant glass fiber breaks into several ultra-fine glass fibers, the ultra-fine glass fibers are wrapped with flame retardant materials to reduce the possibility of glass fiber combustion and further enhance the flame retardant effect.

[0008] Optionally, the flame retardant material is one or a combination of mica flakes, graphene, modified montmorillonite, aluminum hydroxide, and magnesium hydroxide.

[0009] Mica flakes, graphene, modified montmorillonite, aluminum hydroxide, and magnesium hydroxide are used as flame retardant materials and covered on the ultrafine glass fibers. As non-flammable materials themselves, they are covered on the surface of the ultrafine glass fibers, which can prevent the ultrafine glass fibers from contacting with the air, thereby destroying the combustion conditions and delaying the combustion of the ultrafine glass fibers. At the same time, mica flakes, graphene, modified montmorillonite, aluminum hydroxide, and magnesium hydroxide are added as fillers to help improve the mechanical properties of polyamide flame retardant plastics.

[0010] Optionally, each portion of the flame retardant material comprises the following raw materials in parts by weight: 3-5 parts of mica flakes, 5-7 parts of graphene, and 1-2 parts of a cross-linking agent.

[0011] Adding ultrafine mica powder to polyamide can improve its mechanical strength, enhance toughness, adhesion, anti-aging and corrosion resistance. Adding graphite to polyamide can increase its hydrophobicity and mechanical properties. At the same time, mica sheets and graphene are both layered structures. Under the action of cross-linking agents, they can be covered layer by layer on the ultrafine glass fibers at the surface level. Because they are not easy to burn, they have good flame retardancy and can better isolate the flame from the ultrafine glass fibers when an external flame is burning, reducing the possibility of ultrafine glass fibers burning, thereby reducing the probability of the "wick effect".

[0012] Optionally, the ultrafine glass fiber has a diameter of 1-4 μm.

[0013] The diameter of the ultrafine glass fiber is controlled to prevent the diameter of the flame-retardant glass fiber obtained by processing the ultrafine glass fiber from being too large, which makes it difficult to disperse evenly in the modified polyamide flame-retardant plastic.

[0014] Optionally, the ultrafine glass fibers are chopped glass fibers with a length of 3-5 mm.

[0015] Controlling the length of the ultrafine glass fiber allows the flame-retardant glass fiber to split into shorter lengths after being heated. After the flame-retardant material on the outside of the ultrafine glass fiber fails, it can also prevent the ultrafine glass fiber from being too long to form a long duct to achieve the "wick effect", which can better avoid the occurrence of the "wick effect" and enhance the flame retardant ability.

[0016] Optionally, the composite glass fiber further comprises milled glass fiber, and the weight ratio of the milled glass fiber to the flame-retardant glass fiber is 1:(1.5-2.5).

[0017] Milled glass fiber is the product of grinding glass fiber raw silk with hammer machine, ball mill and other crushing equipment. Observed under a microscope, milled glass fiber is composed of columnar glass. Adding milled glass fiber as filler in composite glass fiber can connect with polyamide material to enhance the mechanical properties of composite glass fiber. Milled glass fiber communicates with adjacent flame-retardant glass fibers to construct a network system of composite glass fibers, reducing the possibility of a single flame-retardant glass fiber as a conduit causing a "wick effect" and improving the flame retardant effect.

[0018] Optionally, the particle size of the milled glass fiber is 15-25 mesh.

[0019] The particle size of the milled glass fibers is controlled to facilitate the formation of a composite glass fiber network system.

[0020] Optionally, each portion of the adhesive comprises the following raw materials in parts by weight: 70-100 parts of resin adhesive, 5-7 parts of starch, 1-2 parts of sodium isooctanoate, and 1-2 parts of sodium hydroxide.

[0021] The adhesive is Loctite Hysol E-30CL epoxy resin glue, starch enhances the bonding strength between the glass fibers, sodium hydroxide promotes starch gelatinization to enhance the bonding strength, and sodium isooctanoate increases the drying speed of the adhesive.

[0022] On the other hand, the present disclosure provides a process for preparing a modified polyamide flame retardant plastic, comprising the following steps:

[0023] A. According to parts by weight, the polyamide resin and the toughening agent are stirred uniformly at a speed of 50 to 100 rpm to obtain material A;

[0024] B. Add lubricant, antioxidant, flame retardant and heat stabilizer to material A in parts by weight, mix and stir at 100-150 rpm to obtain mixed material B;

[0025] C. Put the mixed material B into a twin-screw extruder, feed the composite glass fiber from the side port, set the screw speed to 200rpm-300rpm, the main feeding rate to 10-15Hz, and the barrel temperature to 150-250℃ for melt extrusion and granulation to obtain a modified polyamide flame-retardant plastic.

[0026] Through the above method, the composite glass fiber is evenly distributed in the modified polyamide flame retardant plastic, thereby enhancing the flame retardant effect while ensuring the mechanical properties.

[0027] Optionally, the steps for preparing the composite glass fiber are as follows:

[0028] A1: Add mica flakes, graphene and a cross-linking agent to the dispersion according to weight parts, and stir evenly to form a suspension;

[0029] A2: Weigh out 1 part by weight of ultrafine glass fiber and 1.5 parts by weight of suspension, spray the suspension on the ultrafine glass fiber, let it stand and dry, and obtain ultrafine glass fiber wrapped with flame retardant material;

[0030] A3: Mixing a resin adhesive, starch, sodium isooctanoate, and sodium hydroxide according to parts by weight to prepare an adhesive;

[0031] A4: Weigh out 1 part by weight of the ultra-fine glass fiber wrapped with flame retardant material and 0.5 part by weight of adhesive, spray the adhesive on one quarter of the ultra-fine glass fiber wrapped with flame retardant material by spraying method, then add the remaining three quarters of the ultra-fine glass fiber wrapped with flame retardant material, shake and mix, and then let stand to dry;

[0032] A5: Screen out single flame-retardant glass fiber with a diameter of 10-20μm through the sieve;

[0033] A6: According to parts by weight, the chopped glass fiber and the flame retardant glass fiber are mixed to prepare a composite glass fiber.

[0034] Through this method, the adhesive can be evenly wrapped on the ultra-fine glass fiber to form the flame-retardant glass fiber, the flame-retardant glass fiber is screened to a suitable diameter, and then mixed with the glass milled fiber to form the required composite glass fiber.

[0035] Other features and advantages of the present disclosure will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0036] The following is a detailed description of the specific embodiments of the present disclosure. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0037] Preparation example:

[0038] Preparation Example 1:

[0039] The composite glass fiber is prepared by the following steps:

[0040] A1: Add 3 parts of mica flakes, 7 parts of graphene and 1 part of cross-linking agent to the dispersion according to weight, and stir evenly to form a suspension;

[0041] A2: Weigh out 1 part by weight of ultrafine glass fiber and 1.5 parts by weight of suspension, spray the suspension on ultrafine glass fiber with a length of 3 mm and a diameter of 1 μm, and let it stand to dry to obtain ultrafine glass fiber wrapped with flame retardant material;

[0042] A3: 100 parts of resin adhesive, 5 parts of starch, 1 part of sodium isooctanoate, and 1 part of sodium hydroxide were mixed according to weight parts to prepare an adhesive;

[0043] A4: Weigh out 1 part by weight of the ultra-fine glass fiber wrapped with flame retardant material and 0.5 part by weight of adhesive, spray the adhesive on one quarter of the ultra-fine glass fiber wrapped with flame retardant material by spraying method, then add the remaining three quarters of the ultra-fine glass fiber wrapped with flame retardant material, shake and mix, and then let stand to dry;

[0044] A5: Screen out a single flame-retardant glass fiber with a diameter of 10 μm through a sieve;

[0045] A6: According to parts by weight, 25-mesh pulverized glass fiber and flame-retardant glass fiber were mixed in a ratio of 1:2.5 to prepare composite glass fiber.

[0046] Preparation Example 2:

[0047] The composite glass fiber is prepared by the following steps:

[0048] A1: Add 5 parts of mica flakes, 5 parts of graphene and 2 parts of cross-linking agent to the dispersion according to weight parts, and stir evenly to form a suspension;

[0049] A2: Weigh out 1 part by weight of ultrafine glass fiber and 1.5 parts by weight of suspension, spray the suspension on ultrafine glass fiber with a length of 5 mm and a diameter of 4 μm, and let it stand to dry to obtain ultrafine glass fiber wrapped with flame retardant material;

[0050] A3: 100 parts of resin adhesive, 5 parts of starch, 1 part of sodium isooctanoate, and 1 part of sodium hydroxide were mixed according to weight parts to prepare an adhesive;

[0051] A4: Weigh out 1 part by weight of the ultra-fine glass fiber wrapped with flame retardant material and 0.5 part by weight of adhesive, spray the adhesive on one quarter of the ultra-fine glass fiber wrapped with flame retardant material by spraying method, then add the remaining three quarters of the ultra-fine glass fiber wrapped with flame retardant material, shake and mix, and then let stand to dry;

[0052] A5: Screen out a single flame-retardant glass fiber with a diameter of 10 μm through a sieve;

[0053] A6: According to parts by weight, 25-mesh pulverized glass fiber and flame-retardant glass fiber were mixed in a ratio of 1:2.5 to prepare composite glass fiber.

[0054] Preparation Example 3:

[0055] The composite glass fibers were prepared by the following steps:

[0056] A1: Add 4 parts of mica flakes, 6 parts of graphene and 1 part of cross-linking agent to the dispersion according to weight, and stir evenly to form a suspension;

[0057] A2: Weigh out 1 part by weight of ultrafine glass fiber and 1.5 parts by weight of suspension, spray the suspension on ultrafine glass fiber with a length of 4 mm and a diameter of 3 μm, and let it stand to dry to obtain ultrafine glass fiber wrapped with flame retardant material;

[0058] A3: 100 parts of resin adhesive, 5 parts of starch, 1 part of sodium isooctanoate, and 1 part of sodium hydroxide were mixed according to weight parts to prepare an adhesive;

[0059] A4: Weigh out 1 part by weight of the ultra-fine glass fiber wrapped with flame retardant material and 0.5 part by weight of adhesive, spray the adhesive on one quarter of the ultra-fine glass fiber wrapped with flame retardant material by spraying method, then add the remaining three quarters of the ultra-fine glass fiber wrapped with flame retardant material, shake and mix, and then let stand to dry;

[0060] A5: Screen out a single flame-retardant glass fiber with a diameter of 10 μm through a sieve;

[0061] A6: According to parts by weight, 25-mesh pulverized glass fiber and flame-retardant glass fiber were mixed in a ratio of 1:2.5 to prepare composite glass fiber.

[0062] Preparation Example 4:

[0063] The composite glass fiber is prepared by the following steps:

[0064] A1: Add 4 parts of mica flakes, 6 parts of graphene and 1 part of cross-linking agent to the dispersion according to weight, and stir evenly to form a suspension;

[0065] A2: Weigh out 1 part by weight of ultrafine glass fiber and 1.5 parts by weight of suspension, spray the suspension on ultrafine glass fiber with a length of 4 mm and a diameter of 3 μm, and let it stand to dry to obtain ultrafine glass fiber wrapped with flame retardant material;

[0066] A3: Mix 70 parts of resin adhesive, 7 parts of starch, 2 parts of sodium isooctanoate, and 2 parts of sodium hydroxide according to weight parts to prepare an adhesive;

[0067] A4: Weigh out 1 part by weight of the ultra-fine glass fiber wrapped with flame retardant material and 0.5 part by weight of adhesive, spray the adhesive on one quarter of the ultra-fine glass fiber wrapped with flame retardant material by spraying method, then add the remaining three quarters of the ultra-fine glass fiber wrapped with flame retardant material, shake and mix, and then let stand to dry;

[0068] A5: Screen out a single flame-retardant glass fiber with a diameter of 10 μm through a sieve;

[0069] A6: According to parts by weight, 25-mesh pulverized glass fiber and flame-retardant glass fiber were mixed in a ratio of 1:2.5 to prepare composite glass fiber.

[0070] Preparation Example 5:

[0071] The composite glass fiber is prepared by the following steps:

[0072] A1: Add 4 parts of mica flakes, 6 parts of graphene and 1 part of cross-linking agent to the dispersion according to weight, and stir evenly to form a suspension;

[0073] A2: Weigh out 1 part by weight of ultrafine glass fiber and 1.5 parts by weight of suspension, spray the suspension on ultrafine glass fiber with a length of 4 mm and a diameter of 3 μm, and let it stand to dry to obtain ultrafine glass fiber wrapped with flame retardant material;

[0074] A3: Mix 85 parts of resin adhesive, 6 parts of starch, 1.5 parts of sodium isooctanoate, and 1.5 parts of sodium hydroxide according to weight parts to prepare an adhesive;

[0075] A4: Weigh out 1 part by weight of the ultra-fine glass fiber wrapped with flame retardant material and 0.5 part by weight of adhesive, spray the adhesive on one quarter of the ultra-fine glass fiber wrapped with flame retardant material by spraying method, then add the remaining three quarters of the ultra-fine glass fiber wrapped with flame retardant material, shake and mix, and then let stand to dry;

[0076] A5: Screen out a single flame-retardant glass fiber with a diameter of 10 μm through a sieve;

[0077] A6: According to parts by weight, 25-mesh pulverized glass fiber and flame-retardant glass fiber were mixed in a ratio of 1:2.5 to prepare composite glass fiber.

[0078] Preparation Example 6:

[0079] The composite glass fiber is prepared by the following steps:

[0080] A1: Add 4 parts of mica flakes, 6 parts of graphene and 1 part of cross-linking agent to the dispersion according to weight, and stir evenly to form a suspension;

[0081] A2: Weigh out 1 part by weight of ultrafine glass fiber and 1.5 parts by weight of suspension, spray the suspension on ultrafine glass fiber with a length of 4 mm and a diameter of 3 μm, and let it stand to dry to obtain ultrafine glass fiber wrapped with flame retardant material;

[0082] A3: 85 parts of resin adhesive, 6 parts of starch, 1.5 parts of sodium isooctanoate, and 1.5 parts of sodium hydroxide were mixed according to weight parts to prepare an adhesive;

[0083] A4: Weigh out 1 part by weight of the ultra-fine glass fiber wrapped with flame retardant material and 0.5 part by weight of adhesive, spray the adhesive on one quarter of the ultra-fine glass fiber wrapped with flame retardant material by spraying method, then add the remaining three quarters of the ultra-fine glass fiber wrapped with flame retardant material, shake and mix, and then let stand to dry;

[0084] A5: Screen out a single flame-retardant glass fiber with a diameter of 20 μm through a sieve;

[0085] A6: According to parts by weight, 15-mesh pulverized glass fiber and flame-retardant glass fiber were mixed in a ratio of 1:2.5 to prepare composite glass fiber.

[0086] Example:

[0087] Example 1

[0088] A modified polyamide flame-retardant plastic comprises the following raw materials in parts by weight: 50 parts of polyamide resin, 40 parts of composite glass fiber, 1 part of lubricant, 1 part of antioxidant, 1 part of flame retardant, 0.1 part of heat stabilizer, and 1 part of toughening agent. The composite glass fiber comprises flame-retardant glass fiber, and a single flame-retardant glass fiber comprises a plurality of ultrafine glass fibers with flame-retardant material wrapped on the outside, and the plurality of ultrafine glass fibers are bonded by an adhesive to form the flame-retardant glass fiber.

[0089] The polyamide resin is MR-326N supplied by Guangdong 137 Chemical Technology Co., Ltd., the lubricant is EBS10 supplied by Waidian International Chemical Store, the antioxidant is 1010 antioxidant supplied by Lianlong Official Flagship Store, the flame retardant is Doher-6001 flame retardant supplied by Dongguan Doer New Material Technology Co., Ltd., the heat stabilizer is XJ-169IIT heat stabilizer supplied by Chongqing Baohua Chemical Additive Factory, and the toughening agent is Dow's ELVALOYPTW toughening agent.

[0090] The preparation was carried out using the following steps:

[0091] A. According to parts by weight, the polyamide resin and the toughening agent were stirred uniformly at a rotation speed of 50 rpm to obtain material A;

[0092] B. Add lubricant, antioxidant, flame retardant and heat stabilizer to material A according to weight parts, mix and stir evenly at 100 rpm to obtain mixed material B;

[0093] C. The mixed material B is put into a twin-screw extruder, and the composite glass fiber prepared in Preparation Example 1 is fed from the side port. The screw speed is set to 200 rpm, the main feeding rate is 10 Hz, and the barrel temperature is set to 150° C. for melt extrusion and granulation to obtain a modified polyamide flame-retardant plastic.

[0094] Example 2

[0095] A modified polyamide flame-retardant plastic comprises the following raw materials in parts by weight: 70 parts of polyamide resin, 30 parts of composite glass fiber, 2 parts of lubricant, 3 parts of antioxidant, 3 parts of flame retardant, 1 part of heat stabilizer, and 2 parts of toughening agent. The composite glass fiber comprises flame-retardant glass fiber, and a single flame-retardant glass fiber comprises a plurality of ultrafine glass fibers with flame-retardant material wrapped on the outside, and the plurality of ultrafine glass fibers are bonded by an adhesive to form the flame-retardant glass fiber.

[0096] The preparation was carried out using the following steps:

[0097] A. According to parts by weight, the polyamide resin and the toughening agent were stirred uniformly at a rotation speed of 100 rpm to obtain material A;

[0098] B. Add lubricant, antioxidant, flame retardant and heat stabilizer to material A in parts by weight, mix and stir evenly at 150 rpm to obtain mixed material B;

[0099] C. The mixed material B is put into a twin-screw extruder, and the composite glass fiber prepared in Preparation Example 1 is fed from the side port. The screw speed is set to 300 rpm, the main feeding rate is 15 Hz, and the barrel temperature is set to 250° C. for melt extrusion and granulation to obtain a modified polyamide flame-retardant plastic.

[0100] Example 3

[0101] A modified polyamide flame-retardant plastic, the material comprises the following raw materials in parts by weight: 60 parts of polyamide resin, 35 parts of composite glass fiber, 1.5 parts of lubricant, 2 parts of antioxidant, 2 parts of flame retardant, 0.5 parts of heat stabilizer, 1.5 parts of toughening agent, the composite glass fiber comprises flame-retardant glass fiber, a single flame-retardant glass fiber comprises a plurality of ultrafine glass fibers with flame-retardant material wrapped on the outside, and the plurality of ultrafine glass fibers are bonded by an adhesive to form the flame-retardant glass fiber.

[0102] The preparation was carried out using the following steps:

[0103] A. According to parts by weight, the polyamide resin and the toughening agent were stirred uniformly at a speed of 85 rpm to obtain material A;

[0104] B. Add lubricant, antioxidant, flame retardant and heat stabilizer to material A in parts by weight, mix and stir evenly at 125 rpm to obtain mixed material B;

[0105] C. The mixed material B is put into a twin-screw extruder, and the composite glass fiber prepared in Preparation Example 1 is fed from the side port. The screw speed is set to 250 rpm, the main feeding rate is 12.5 Hz, and the barrel temperature is set to 185° C. for melt extrusion and granulation to obtain a modified polyamide flame-retardant plastic.

[0106] Example 4

[0107] The difference from Example 3 is that the composite glass fiber prepared in Preparation Example 2 is used.

[0108] Example 5

[0109] The difference from Example 3 is that the composite glass fiber prepared in Preparation Example 3 is used.

[0110] Example 6

[0111] The difference from Example 3 is that the composite glass fiber prepared in Preparation Example 4 is used.

[0112] Example 7

[0113] The difference from Example 3 is that the composite glass fiber prepared in Preparation Example 5 is used.

[0114] Example 8

[0115] The difference from Example 3 is that the composite glass fiber prepared in Preparation Example 6 is used.

[0116] Example 9

[0117] The difference from Example 3 is that the outer side of the flame retardant glass fiber is wrapped with a magnesium hydroxide flame retardant.

[0118] Example 10

[0119] The difference from Example 3 is that no milled glass fibers were added.

[0120] Comparative Example 1

[0121] The difference from Example 3 is that ordinary commercially available glass fibers are used instead of flame-retardant glass fibers.

[0122] Comparative Example 2

[0123] The difference from Example 3 is that no glass fiber is added.

[0124] Comparative Example 3

[0125] The difference from Example 3 is that 5-10 parts by weight of a flame retardant is added.

[0126] The present invention tests the polyamide UL-94 prepared in the embodiment and the comparative example, and the test method is as follows: UL-94 test vertical combustion test: refer to DINIEC60695-11-10-20 "Plastic Combustion Performance Test Method Horizontal Method and Vertical Method" standard, and use CFZ-5 vertical combustion tester to test at room temperature. Sample bar specification: 125mm*3.2mm*3.2mm.

[0127] At the same time, the tensile strength of the embodiments and comparative examples was tested, and the test standard adopted the test standard of ASTM / D638.

[0128] At the same time, the bending strength of the embodiments and comparative examples was tested, and the test standard adopted the test standard of ASTM / D790.

[0129] At the same time, the Izod notched impact strength of the embodiment and the comparative example was tested, and the test standard adopted the test standard of ASTM / D256.

[0130] Table 1 Test results of properties of modified polyamide flame retardant plastics prepared in Examples 1-10 and Comparative Examples 1-3

[0131]

[0132] Based on Table 1, by comparing the flame retardant properties of Examples 1-10 with Comparative Examples 1-3, it can be seen that the flame retardant properties of Examples 1-10, Comparative Examples 2 and Comparative Example 3 are all V0. It can be seen that by using flame retardant glass fiber, under different ratios disclosed in the present invention, the modified polyamide can achieve good flame retardant effect, while the flame retardant property of Comparative Example 1 is V2. By comparing Example 3 with Comparative Example 1, it can be seen that the use of flame retardant glass fiber helps to improve the flame retardant effect.

[0133] By comparing the tensile strength of Examples 1-10 with that of Comparative Examples 1-3, it can be seen that the difference in tensile strength of Examples 1-10 is 8 MPa, and the average is 89.9 MPa, which is similar to the strength of Comparative Example 1, better than 66 MPa of Comparative Example 2, and better than 71 MPa of Comparative Example 3. Therefore, it can be seen that the scheme of the present disclosure ensures excellent flame retardant properties while keeping the tensile strength brought by the addition of glass fiber roughly unchanged.

[0134] By comparing the bending strength of Examples 1-10 with that of Comparative Examples 1-3, it can be seen that the difference in bending strength of Examples 1-10 is 10 MPa, and the average is 108.9 MPa, which is close to 109 MPa of Comparative Example 1, and significantly better than 87 MPa of Comparative Example 2 and 82 MPa of Comparative Example 3. Therefore, it can be seen that the scheme disclosed in the present invention ensures excellent flame retardant properties while keeping the bending strength brought by the addition of glass fiber roughly unchanged.

[0135] By comparing the Izod notched impact strength of Examples 1-10 and Comparative Examples 1-3, it can be seen that the difference in bending strength of Examples 1-10 is 8 MPa, and the average is 110 MPa, which is close to 112 MPa of Comparative Example 1, and significantly better than 82 MPa of Comparative Example 2 and 84 MPa of Comparative Example 3. Therefore, it can be seen that the scheme disclosed in the present invention ensures excellent flame retardant properties while keeping the Izod notched impact strength brought about by the addition of glass fiber roughly unchanged.

[0136] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A modified polyamide flame retardant plastic, characterized in that: The plastic comprises the following raw materials in parts by weight: Polyamide resin 50-70 parts Composite glass fiber 30-40 parts 1-2 parts lubricant 1-3 parts antioxidant Flame retardant 1-3 parts Heat stabilizer 0.1-1 part 1-2 parts toughening agent The composite glass fiber includes flame-retardant glass fiber, and a single flame-retardant glass fiber includes a plurality of ultrafine glass fibers wrapped with flame-retardant materials on the outside, and the plurality of ultrafine glass fibers are bonded by an adhesive to form the flame-retardant glass fiber, and each portion of the flame-retardant material includes the following raw materials in parts by weight: 3-5 pieces of mica flakes Graphene 5-7 parts 1-2 parts of cross-linking agent; Each portion of the adhesive comprises the following raw materials in parts by weight: Resin adhesive 70-100 parts 5-7 parts starch 1-2 parts of sodium 2-ethylhexanoate 1-2 parts of sodium hydroxide; The steps for preparing composite glass fiber are as follows: A1: Add mica flakes, graphene and a cross-linking agent to the dispersion according to weight parts, and stir evenly to form a suspension; A2: Weigh out 1 part by weight of ultrafine glass fiber and 1.5 parts by weight of suspension, spray the suspension on the ultrafine glass fiber, let it stand and dry, and obtain ultrafine glass fiber wrapped with flame retardant material; A3: Mixing a resin adhesive, starch, sodium isooctanoate, and sodium hydroxide according to parts by weight to prepare an adhesive; A4: Weigh out 1 part by weight of the ultra-fine glass fiber wrapped with flame retardant material and 0.5 part by weight of adhesive, spray the adhesive on one quarter of the ultra-fine glass fiber wrapped with flame retardant material by spraying method, then add the remaining three quarters of the ultra-fine glass fiber wrapped with flame retardant material, shake and mix, and then let stand to dry; A5: Screen out a single flame-retardant glass fiber with a diameter of 10-20 μm through a sieve; A6: According to parts by weight, the chopped glass fiber and the flame retardant glass fiber are mixed to prepare a composite glass fiber.

2. The modified polyamide flame retardant plastic according to claim 1, characterized in that: The diameter of the ultrafine glass fiber is 1-4 μm.

3. The modified polyamide flame retardant plastic according to claim 2, characterized in that: The ultra-fine glass fibers are short-cut glass fibers with a length of 3-5 mm.

4. The modified polyamide flame retardant plastic according to claim 1, characterized in that: The composite glass fiber also includes glass milled fibers, and the weight ratio of the glass milled fibers to the flame-retardant glass fibers is 1:(1.5-2.5).

5. The modified polyamide flame retardant plastic according to claim 4, characterized in that: The particle size of the milled glass fiber is 15-25 meshes.

6. A process for preparing the modified polyamide flame retardant plastic according to any one of claims 1 to 5, characterized in that: The following steps are included: A. According to parts by weight, the polyamide resin and the toughening agent are stirred uniformly at a speed of 50 to 100 rpm to obtain material A; B. Add lubricant, antioxidant, flame retardant and heat stabilizer to material A in parts by weight, mix and stir at 100-150 rpm to obtain mixed material B; C. Put the mixed material B into a twin-screw extruder, feed the composite glass fiber from the side port, set the screw speed to 200rpm-300rpm, the main feeding rate to 10-15Hz, and the barrel temperature to 150-250℃ for melt extrusion and granulation to obtain a modified polyamide flame-retardant plastic.

Citation Information

Patent Citations

  • Flame-retardant graphene master batch for reinforcing foamed plastic, and preparation method thereof

    CN109294091A